USER EXPERIENCE AND DIGITAL ADAPTATION: A QUALITATIVE STUDY OF SHARING ENGLISH LEARNING ACTIVITIES ON TIK TOK AMONG FRESH GRADUATE TEACHERS - Salainti, Engelina; Rotikan, Reymond (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2026)
This study explores the User Experience (UX) and digital adaptation of fresh-graduate English teachers using TikTok to share their experiences of learning activities. Although TikTok is primarily associated with entertainment, a growing number of novice educators are leveraging it as a professional instrument for educational vlogging. This research utilizes a qualitative descriptive approach to investigate the experiences of three recently graduated teachers. Data collection involved semi-structured interviews and observations of their digital content on the TikTok platform. The results reveal a significant shift in the teachers' viewpoints, evolving from a "fun" user to a "responsible" educator. They noted that sharing English language learning activities on TikTok fosters student engagement, considering the platform's connection to students' daily lives. Conversely, the teachers encountered several technical challenges, including "phone lag," "copyright issues" related to audio, and the considerable time demands of video editing. To address these challenges, the educators implemented a blended editing approach, leveraging alternative applications prior to TikTok publication and acquiring knowledge through YouTube instructional content. Despite the technical difficulties encountered, the teachers expressed considerable satisfaction and plan to continue using TikTok in the future. The research also shows that new teachers are very confident in their digital skills. This allows them to use new mobile technologies effectively in their teaching.